Inovasi Layanan Samsat, Pemutihan Pajak Daerah dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor dengan Kesadaran Wajib Pajak Sebagai Variabel Moderasi : Studi Kasus Pada UPT PPD Kediri - Viken Wahyuningsih; Linawati; Badrus Zaman (Jurnal Literasi Akuntansi, 2026)
Purpose: This study aims to examine the effect of Samsat service innovation, regional tax amnesty, and tax sanctions on motor vehicle taxpayer compliance, with taxpayer awareness as a moderating variable at UPT Pengelolaan Pendapatan Daerah (PPD) Kediri. Method: This study employed a quantitative approach using primary data collected through questionnaires distributed to motor vehicle taxpayers registered at UPT PPD Kediri. The data were analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and Moderated Regression Analysis (MRA). Finding: The results indicate that Samsat service innovation, regional tax amnesty, and tax sanctions have a positive and significant effect on motor vehicle taxpayer compliance. Taxpayer awareness is unable to strengthen the effect of Samsat service innovation and regional tax amnesty on taxpayer compliance. However, taxpayer awareness is proven to strengthen the effect of tax sanctions on motor vehicle taxpayer compliance. Novelty: This study integrates taxpayer awareness as a moderating variable in examining the relationship between Samsat service innovation, regional tax amnesty, tax sanctions, and motor vehicle taxpayer compliance. The study also provides empirical evidence from UPT PPD Kediri regarding the effectiveness of fiscal policies and taxpayer behavior.